The importance of disappointment - Craib, Ian, 1945- (Routledge, 1994)
This book explores the nature of identity in late modern society, arguing that new possibilities of living, such as 'personal growth', are in fact illusions. This is shown by examining modern theories of death and ideas of masculinity.